Natural history of bothrops itapetiningae boulenger, 1907 (serpentes: Viperidae: crotalinae), an endemic species of the Brazilian Cerrado - Muniz Leao, Suelem (2014)
We present data on habitat use, activity, sexual dimorphism, reproduction, and diet of Bothrops itapetiningae, a species endemic to the Brazilian Cerrado. Habitat use was studied through active search techniques in several areas from July 1997 to July 2000. Diet, reproduction, activity, and sexual dimorphism were studied through the analysis of specimens deposited in Brazilian museums. Annual activity was inferred from collection records grouped by month and season. The specimens were sexed by direct observation of gonads and sexual dimorphism was assessed using morphological data. The reproductive cycle of the species was studied by analyzing the number of vitellogenic and nonvitellogenic follicles, ova, and embryos by month. The diet was determined by analyzing stomach and digestive tract contents. The species is a habitat specialist, associated with open cerrado grasslands, and is active more frequently during the rainy season (October to March). Males have longer tails whereas females have longer heads. The reproductive cycle is seasonal and probably biennial, with births (5.8 ± 2.9 embryos) occurring during the rainy season. Diet is of a generalist, but mammals are important items for both sexes and all age classes. Bothrops itapetiningae is among the smaller Brazilian pit vipers. Its low fecundity, high habitat specialization, and sensitivity to human disturbances, along with the high level of threat to its natural grassland habitat in the Brazilian Cerrado, makes this a potentially threatened snake. Knowledge of its biology is fundamental to conserving and managing this species.